The Impact of Ultrasound-Guided Subcostal Transversus Abdominis Plane (SCTAP) Block on Postoperative Pain Relief in a Patient Undergoing Cholecystectomy: A Case Report - Sucipto, Priskila Wulan; Marilaeta Cindryani Ra Ratumasa (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Handling post-operative pain in cholecystectomy requires several considerations, especially in terms of pain management. Various multimodal analgesia strategies to optimize postoperative pain control include epidural catheter placement, intravenous opioids, and the recently introduced ultrasonography (USG)-guided subcostal transversus abdominis plane (SCTAP) block. This case report aims to describe the postoperative analgesic effectiveness of ultrasound-guided SCTAP block in a patient undergoing open cholecystectomy. Case presentation: A 57 year old female patient with a diagnosis of multiple cholelithiasis, cholecystitis, was planned to undergo cholecystectomy, under general anesthesia and SCTAP block, with an ultrasound probe placed under the costal margin, the transversus abdominis muscle fascia was identified and local anesthetic infiltration laterally with bupivacaine plain 0.25 % 20 ml each on the left and right sides. Postoperatively, the patient returned to the room and received oral analgesics without opioids for pain management. Conclusion: Ultrasound-guided SCTAP blocks provide effective postoperative analgesia, reduce the need for postoperative analgesics, while supporting recovery after open cholecystectomy.